Carbon stocks in coarse woody debris in the middle taiga ecosystems located along the Yenisei river - Klimchenko, Alexander V.; Verkhovets, Sergey V. (Zenodo, 2012)
This paper presents the results of the assessment of carbon stocks in the coarse woody debris in the prevailing forest types of the middle taiga. Carbon stocks in down coarse woody debris were estimated to total 58.2 million tonnes, 80% of which were found in dark conifer stands, 10% in deciduous forests, and 10% in pine forests and pine logging. In pine forests of the two dominant groups of forest types and pine logging, carbon stocks amounted to 1.5– 3.3 and 1.2 million tonnes, respectively. The values obtained in this study will be used to develop a database on ecosystem components required for quantifying carbon storage and fluxes.